2004
DOI: 10.1038/sj.onc.1207930
|View full text |Cite
|
Sign up to set email alerts
|

Self-renewal of teratocarcinoma and embryonic stem cells

Abstract: Pluripotent stem cells derived from preimplantation embryos, primordial germ cells or teratocarcinomas are currently unique in undergoing prolonged symmetrical self-renewal in culture. For mouse embryonic stem (ES) cells, self-renewal is dependent on signals from the cytokine leukaemia inhibitory factor (LIF) and from either serum or bone morphogenetic proteins (BMPs). In addition to the extrinsic regulation of gene expression, intrinsic transcriptional determinants are also required for maintenance of the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
358
0
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 485 publications
(377 citation statements)
references
References 93 publications
13
358
0
6
Order By: Relevance
“…In undifferentiated mES cells, ERβ was expressed constitutively at relatively low levels. We estimated approximately 400 ERβ molecules per cell by ligand binding assay using 3 H-E 2 (data not shown). ERα was not expressed in undifferentiated mES cells or in the immediate 5 days following LIF withdrawal, but was expressed by day 7-8 in EBs (Figure 1; immunohistochemistry data not shown).…”
Section: Mechanism Of Pr Gene Induction During Differentiation Inducementioning
confidence: 99%
See 1 more Smart Citation
“…In undifferentiated mES cells, ERβ was expressed constitutively at relatively low levels. We estimated approximately 400 ERβ molecules per cell by ligand binding assay using 3 H-E 2 (data not shown). ERα was not expressed in undifferentiated mES cells or in the immediate 5 days following LIF withdrawal, but was expressed by day 7-8 in EBs (Figure 1; immunohistochemistry data not shown).…”
Section: Mechanism Of Pr Gene Induction During Differentiation Inducementioning
confidence: 99%
“…Embryonic stem (ES) cells are defined by the properties of pluripotency and self-renewal, and are capable of differentiating into cell lineages from all three germ layers as well as into germ cells [1][2][3][4][5]. They are derived from the inner cell mass of blastocysts and provide a powerful model system to study the molecular mechanisms regulating early and late lineage specific differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…bFGF provides an important medium component for culture of cow (Gjørret and MaddoxHyttel, 2005), pig (Li et al, 2004) and all three fish species (see Table 3), but not mouse ESCs (Chambers and Smith, 2004). Therefore, FGF may have variable success as a media supplement for other species.…”
Section: Media Supplementsmentioning
confidence: 99%
“…LIF, a member of the Interleukin (IL-6) family of cytokines, signals through receptor complexes including the transmembrane receptor gp130 (Chambers and Smith, 2004). Mouse LIF is dispensable for primate ESC (Carpenter et al, 2003) but vital for nonprimate mammals (excluding the dunnart) and chicken ESC cultures.…”
Section: Media Supplementsmentioning
confidence: 99%
“…In order to be able to exploit the rapid culture methods and safety of hESCs and hiPSCs for therapeutic purposes, it will be important to elucidate the molecular mechanisms that control the self-renewal and differentiation of ESCs. Many factors that control ESC pluripotency have now been identified and it has been demonstrated that an appropriate balance among several extrinsic signaling pathways is required for the maintenance of pluripotency [6][7][8]. However, the underlying molecular mechanisms that determine the regulation of these extrinsic signaling pathways in ESCs remain unknown.…”
Section: Introductionmentioning
confidence: 99%